Inter-Institutional Dynamics for Appropriate Technology in Northern Argentina - Camprubi, Germán (2023)
The objective of this article is to present an interactive dynamic between heterogeneous organizational actors to resolve the need for mechanization of weed removal in northern Argentina. The methodological strategy applied was single case study with a constructivist vision of technology and, specifically, with the approaches of Appropriate Technologies (AT) and the Quadruple Helix model. The codified knowledge of engineering was a necessary, but insufficient condition for the manufacture of a machine in a period of 3 years. The main contribution consists of presenting a hybrid product as a result of the interaction between producers, an SME and the University in a proximity network to which the State joined as a financing entity with auditor and regulatory functions. A practical implication is that the interinstitutionality was grounded in the individual scales of its representatives. In parallel, the relational dynamics between individual agents was a leverage point for the tangible and intangible results achieved in the territory.